The Influence of Self-Efficacy and Peer Conformity on Cheating Behavior - Putri, Ananda Zahrani; Eryanto, Henry; Rachmadania, Rizki Firdausi (Politeknik Assalaam Surakarta, 2025)
This study aims to analyze the influence of self-efficacy and peer conformity on cheating behavior in Class X vocational high schools in Jakarta. This research applies a quantitative approach through survey methods. The population used consisted of 180 students, with a sample of 120 students obtained through the proportional random sampling technique. Data collection with a questionnaire using a Likert scale. The data analysis method IBM SPSS Statistics Version 26 was used in this study. The study findings indicate that the self-efficacy variable and the cheating behavior variable have a partial relationship, as evidenced by the t-value -12.080 > t-table value -1.658. The peer conformity variable shows a partial relationship with the cheating behavior variable, as evidenced by the t-value 11.292 > the t-table value 1.658. The simultaneous test results indicate that the self-efficacy variable and peer conformity have a simultaneous relationship with the cheating behavior variable, F-value 400.124 > F-table value 3.07. Implications of this study: (1) Cheating behavior variable have the highest percentage indicator, time 30%. This indicates that students cheat during certain periods, such as the last minutes before the exam paper is collected, when the teacher is busy, there is no exam supervisor, or when the teacher is not paying attention to them. (2) Self-efficacy variable has the highest percentage indicator in generality at 33.6%. This indicates that low self-efficacy among students affects their lack of focus in class due to a heavy homework load, difficulty in recovering from failure, and reluctance to try again. (3) The peer conformity variable was found to have the highest percentage indicator, namely individual agreement within the group, at 33.4%. That students are united in telling the teacher they forgot to do the homework, united in not doing the teacher's homework, or united in collaborating during the exam.